Landfill Site Selection of Savar Municipality, Bangladesh: A Multi Criteria Evaluation Approach - F. Reza; Dr. A. N. Kakon; Md. Z. Haq (Lowland Technology International, 2016)
Landfill has been recognized as the cheapest and more acceptable form for the final disposal of municipal solid waste and as such has been the most used method in the world. Selection of appropriate landfill site is a complex task as the selection process involves many criteria. This paper presents the landfill site selection process of Savar Municipality. Initially, area required for future landfill site has been estimated considering without waste composting and with different percentages of composting. The estimation shows that, 4.09 to 9.96 acres of land will be required annually by 2025 for landfill. Then Multi Criteria Evaluation (MCE) approach has been used to identify suitable sites for landfill. After having set-up of selected criteria, scaling of criteria and weighting of criteria; suitability scores for eight landfill sites have been calculated. Two landfill sites have been chosen on the basis of their higher suitability score.